Instagram and Students' Higher Order Thinking Skill of Creating - Agrikaltarini, Niken Dwiretno Galuh; Susanto, Susanto; Munir, Ahmad (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
It is a qualitative study that focuses on how students apply their creating skill as seen in their compositions posted on Instagram. There were six tenth graders in one of the vocational high schools in Sidoarjo selected as the participants. They comprised three male students and three female students. The researcher collected the data in the form of written expressions (sentences) by observing students’ creating skill processes as seen in their compositions posted on Instagram. The data thenwere analyzedusing the elements of each Brookhart’s HOT skills of transfer, critical thinking, and problem-solving. The findings showed that the activities of composing narrative texts and posting them on the Instagram account belong to the real and meaningful transfer learning of near and far transfers. Next, students could fulfill seven out of eleven criteria of critical thinkingskill. Last, from five components of the IDEAL problem-solving skill, only the last component of looking back andevaluatingthe effects of the activity that the students did not do. All in all, theactual evidence of creating skill implementation when students created their compositions by using Instagram is possible to justify.